Advances in Tumor Targeting Biomimetic Drug Delivery Systems: A Promising Approach for Antitumor Therapy - Mo, Ziyi; He, Jiao; Li, Man; Guo, Rong; He, Qin (Pharmaceutical Fronts, 2024)
Cancer is one of the most fatal diseases that attract numerous efforts and attention from researchers. Among plentiful therapeutic agents, chemotherapy is frequently used in treating virulent tumors, and its insistent administration is useful in the ablation of cancers; however, it also produces side effects. Biomimetic drug delivery systems (BDDSs) provide an alternative route for antitumor therapy. Their endogenous substances may be extracellular vesicles, living cells, cell membranes, etc., which optimize single-agent chemotherapy. They “upgrade” traditional drug delivery platforms by combining the original drug with itself, disguised as a Trojan Horse, to trick the immune system or tumor tissues to achieve higher targeting and lower immunogenicity. Herein, we review three BDDS strategies being used recently in antitumor drug development and their advances, aiming at providing general guidelines and opportunities in this field in the future.
Keywords: biomimetic drug delivery system; antitumor; nanoparticles; endogenous substances